Peningkatan Keterampilan Menulis Narasi Melalui Model Pembelajaran Picture and Picture pada Peserta Didik Kelas IV SDN Dukuh Kupang II/489-Surabaya - Astiya Nur Laili; Bekti Wirawati (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to improve the narration writing skills through a picture and picture learning model for the students of Class IV in SDN Dukuh Kupang II Surabaya. This research is a Classroom Action Research (CAR). The subject of this research is the students of Class IV in SDN Dukuh Kupang Surabaya, a total of 28 students. The method used in this research is descriptive quantitative. The techniques used to collect data in this research are tests and observation. The data analysis techniques used are test data and observation data analysis. The result is success portrayed by the improvement of pre-cycle I and II results. On the pre-cycle, the students obtain an average score of 65.89 with a percentage of 42%. Meanwhile, on cycle I, the average score resulted in 77.76 with a percentage of 78%. Then, there is another escalation on cycle II with the average score result being 86.60 with a percentage of 92%. In conclusion, this research shows that there is an improvement in the narration writing skills through the picture and picture learning model in the students of Class IV in SDN Dukuh Kupang Surabaya.